2013
DOI: 10.1111/ggi.12098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural characteristics and outcome quality indicators at health care facilities for the elderly requiring long‐term care in Japan from a nationwide survey

Abstract: Aim:To clarify the performance situation of selected quality indicators: falls, pressure ulcers and dehydration, at health care facilities for the elderly in Japan, and what structural characteristics are related to them. Methods:The operational population consisted of 1057 institutionalized users (approximately 10 randomly selected per facility) from a survey answered by the care staff. The facilities were divided into two groups according to their prevalence of negative outcomes (falls, pressure ulcers, dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
0
14
0
7
Order By: Relevance
“…We included years in business, facility size (<100 beds, 100 beds or >100 beds), location (metropolitan, non-metropolitan), the availability of 24-h nursing staff and the number of staff in different specialties allocated per 100 users, the proportion of registered nurses (RN) among nurses, and the proportion of registered dietitians among all dietitians. 9,13,14,22 We also included an independent variable that indicated the types of care facilities provide in terms of traditional, unit or mixed. Traditional care is mainly provided in facilities with a shared room setting.…”
Section: Facility-level Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included years in business, facility size (<100 beds, 100 beds or >100 beds), location (metropolitan, non-metropolitan), the availability of 24-h nursing staff and the number of staff in different specialties allocated per 100 users, the proportion of registered nurses (RN) among nurses, and the proportion of registered dietitians among all dietitians. 9,13,14,22 We also included an independent variable that indicated the types of care facilities provide in terms of traditional, unit or mixed. Traditional care is mainly provided in facilities with a shared room setting.…”
Section: Facility-level Characteristicsmentioning
confidence: 99%
“…However, previous studies have shown that facility service users were more likely to experience a deterioration in the care‐need level than community‐based service and home care service users . To the best of our knowledge, only one study has analyzed the facility characteristics that are associated with the outcome indicators, but no study has investigated the facility characteristics that are associated with care‐need level deterioration …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate nurse staffing levels are critical to NH residents' quality of care outcomes. Different levels of nurse staffing, skill-mix, and TN hours have been studied as predictors of falls among the NH residents and hospital patients (Backhaus et al, 2016;Cho et al, 2016;Sandoval Garrido et al, 2014;He et al, 2016;Horn et al, 2016;Kalisch & Tschannen, 2012;Leland et al, 2012;Schuelke, Young, Folkerts, & Hawkins, 2014;Shin & Hyun, 2015;. In NHs, impact of nurse staffing levels on falls incidences were examined using total nurse HPRD and RN skill-mix (Backhaus et al, 2016), RN, RN skill-mix, and CNA HPRD (Shin & Hyun, 2015), CNA (Horn et al, 2016), TN HPRD (Sandoval Garrido et al, 2014), and CNA and LN HPRD (Leland et al, 2012).…”
Section: The Relationship Between Nurse Staffing Standards/levels Andmentioning
confidence: 99%
“…The two assessments may differ in many ways, including their goals and units of assessment as well as the stakeholders and audience of the evaluations. There are a few existing frameworks for LTCSPA in the United States, Canada, Europe, Japan and South Korea, some of which were proposals only while others were implemented [6][7][8][9][10][11]. The frameworks have shared goals to better understand their LTC system(s) and to inform various stakeholders of their performance.…”
Section: Introductionmentioning
confidence: 99%